2004
DOI: 10.1057/palgrave.ces.8100049
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Federalism in Russia: Rules versus Electoral Politics

Abstract: This paper examines the determinants of financial flows between the federal government and regional authorities in Russia. The main question is to what extent intergovernmental transfers correspond to the ‘ideal pattern’ – equalisation of the abilities of the regions to provide public goods – and to what extent, if at all, they reflect the influence of federal–regional political discourse (asymmetrical federalism). The main finding is that actual net transfers since 1994, although quite close to the ‘ideal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…For some regions it accounts for a big portion of their total transfer. This result goes in line with Popov's (2004) finding that the federal government awarded its loyal supporters with transfers. Third, we find no evidence for the grantsmanship hypothesis: neither governor's tenure, no elected governor dummy turned out to be significant.…”
Section: -1998supporting
confidence: 80%
See 2 more Smart Citations
“…For some regions it accounts for a big portion of their total transfer. This result goes in line with Popov's (2004) finding that the federal government awarded its loyal supporters with transfers. Third, we find no evidence for the grantsmanship hypothesis: neither governor's tenure, no elected governor dummy turned out to be significant.…”
Section: -1998supporting
confidence: 80%
“…Daniel Treisman (1996, 1998aand 1998b found that receipts by regions of federal transfers in 1992-1996 were a positive function of anti-incumbent voting, and also of protest actions by the region -sovereignty declarations, and strikes. On the contrary, the study by Vladimir Popov (2004) found that during 1995-2001 net transfers were positively related to the pro-Yeltsin vote and pro-democratic results of the parliamentary elections.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…There is a substantial literature linking interbudgetary grants to loyalty of Russian regions to the center (Treisman, 1996(Treisman, , 1998Solanko, 1999;Popov, 2004;Jarocinska, 2004;Dombrovsky, 2006): the question is whether it is the "loyal" or the "secessionist" regions receiving higher amount of funds, but for the purposes of this paper it is sufficient that the link might exist. Higher declared autonomy may as well have an impact on political process and thus on democratization levels.…”
Section: Extreme Bounds Analysismentioning
confidence: 99%
“…The question most often asked has been whether the goal of federal transfers is to attain such economic objectives as the equalization of fiscal capacity and expenditure needs among different levels of governments, or whether they actually reflect political economy considerations and purely asymmetric treatment and are governed by the political forces of the moment. Popov (2002), Treisman *2 a u, « ( 1996,2000) and others find that politics have been a major force in defining federal transfers to the regions, though the relevant political factors may have changed over time. For example, Treisman (1996) concludes that early on, the central government used federal transfers to appease troublemaking regions.…”
Section: What Has Driven Federal Transfers To the Regions?mentioning
confidence: 99%